2020
DOI: 10.1016/j.scitotenv.2020.139401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concentrated poultry operations and cropland manure application on antibiotic resistant Escherichia coli and nutrient pollution in Chesapeake Bay watersheds

Abstract: Nitrogen concentrations in watersheds increased with numbers of poultry barns in and around the watershed. • Cephalosporin-resistant E. coli in streams was positively correlated with the estimated poultry manure exposure. • Studying small watersheds has the potential to reveal sources of antibiotic resistant bacteria and nutrient pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…In runoff waters from litter‐amended soils, we observed increases of LAB, and this result is consistent with previously identified risks of litter application to downstream water resources (Amato et al., 2020; Hoover et al., 2019; Hubbard et al., 2020). To evaluate if prairie strip installations could attenuate these indicators, we compared the reduction of LAB and ARGs in littered plots with and without strips.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In runoff waters from litter‐amended soils, we observed increases of LAB, and this result is consistent with previously identified risks of litter application to downstream water resources (Amato et al., 2020; Hoover et al., 2019; Hubbard et al., 2020). To evaluate if prairie strip installations could attenuate these indicators, we compared the reduction of LAB and ARGs in littered plots with and without strips.…”
Section: Discussionsupporting
confidence: 92%
“…Treatments are crop with strip (CS), crop with strip and litter application (CSL), and crop and litter application (CL). Antibiotic resistance genes unique to litter are denoted with an asterisk previously identified risks of litter application to downstream water resources (Amato et al, 2020;Hoover et al, 2019;Hubbard et al, 2020). To evaluate if prairie strip installations could attenuate these indicators, we compared the reduction of LAB and ARGs in littered plots with and without strips.…”
Section: Discussionmentioning
confidence: 99%
“…The studies which used genotyping methods are summarized in Table 1, and they indicate that fecally contaminated watermainly surface waters and wastewater-are an important source of UPEC. 20,[29][30][31][32][33][34][35][36][37] Zhi et al 38,39 identified pUPEC by screening wastewater samples from treatment plants in Alberta, Canada, for E. coli containing at least three of five UPEC virulence genes. When the researchers compared pUPEC with known UPEC from UTIs from international databases, they found > 96% whole genome similarity; one isolate demonstrated 99.5% genome similarity.…”
Section: Evidence Of Putative Upec In Watermentioning
confidence: 99%
“…There is a direct link between poultry house concentration in the Delmarva region and the amount of nutrient pollution in the watershed of the Chesapeake Bay (Amato et al 2020). Over the last several decades, broiler production has experienced significant growth, and its operations have spread throughout the watershed.…”
Section: Longo Et Al | Nutrient Overloading In the Chesapeake Baymentioning
confidence: 99%
“…The poultry industry in the whole watershed produces over 185 million pounds of nitrogen and over 50 million pounds of phosphorous each year (Chesapeake Bay Foundation 2004). While production on the Delmarva Peninsula produces only a portion of this total, with its large number of facilities and its growth and intensification over the last several decades, it is a significant contributor to nutrient pollution in the Chesapeake Bay (Amato et al 2020;Ator, Brakebill, and Blomquist 2011).…”
Section: Integration Labor and Environmental Changementioning
confidence: 99%